Mastering financial modeling : a professional's guide to building financial models in Microsoft Excel - Soubeiga, Eric (McGraw-Hill Education, 2013)
All the precision of financial modeling--and none of the complexity Evidence-based decision making is only as good as the external evidence on which it is based. Financial models uncover potential risks on a company's balance sheet, but the complexity of these instruments has limited their effectiveness. Now, Mastering Financial Modeling offers a simplified method for building the fast and accurate financial models serious evidencebased decision makers need. What sets this practical guide apart is its "learning-on-the-job" approach. Unlike other books that teach modeling in a vacuum, this superior method uses a diverse collection of case studies to convey each step of the building process. "Learning on the job" connects the dots between the proper Excel formulas and functions and the real-world situations where you want to use them. By learning through association, you can absorb the information quickly and have it ready to use when you need it. The book starts right off on building models--from creating a standalone cash flow model through integrating it with an income statement and balance sheet. Along the way, you will master the skill set you need to build advanced financial models. With only a basic knowledge of accounting and finance, individual investors and financial professionals alike can: Create a core model and customize it for companies in most industries Understand every working component of a financial model and what each one tells you about a company Format cells and sheets in Excel for easily repeatable modeling Written with the practitioner in mind, Mastering Financial Modeling shows you how to ensure your model is ready for real-world application by safeguarding it against modeling errors. It covers a full array of Excel's builtin auditing and testing tools and illustrates how to build customized error-checking tools of your own to catch the inaccuracies that typically fall through the cracks. Get the most out of your data with Mastering Financial Modeling . Mastering Financial Modeling brings the power of financial models down to earth and puts it in the hands of investors, bankers, and private equity professionals who don't have a passion for crunching numbers. Nowhere else can you get step-by-step instruction on building these valuable tools from an elite World Bank investment officer. Starting from the ground up, Eric Soubeiga shows you how to interpret and build financial models in Microsoft Excel that will accurately a ...